Marketing Strategy to Increase Consumer Purchase Interest at CV. Mitra Agung, Sungai Pinyuh District - Atika Sulastri; Yuni firayanti; Marhamah Marhamah (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study aims to analyze the marketing strategies implemented by CV Mitra Agung to increase consumer purchasing interest in the Sungai Pinyuh District. Using a qualitative descriptive approach, data collection was conducted through in-depth interviews, direct observation, and documentation studies. The results of the analysis indicate that the implementation of an integrated marketing mix (product, price, place, and promotion) has been significantly successful in increasing both consumer purchasing interest and loyalty. The main supporting factors for this success include offering products with consistent quality, setting competitive prices compared to competitors, active and creative promotions, especially through the use of social media, and selecting a strategic and easily accessible business location. Despite showing positive results, this study also identified several challenges faced by the company, namely limited operational capital and limited market reach, which need to be addressed for future business development. Based on these findings, several important recommendations are provided, These include continuous innovation in product variants, optimizing and maximizing the use of digital media platforms to increase brand awareness, and improving the quality of customer service. These recommendations are expected to help CV Mitra Agung expand its market share, improve sales performance, and ensure business sustainability.